Spatial Dimensions of Tower Karst and Cockpit Karst: A Case Study of Guilin, China - (:unkn) unknown (My University, 2014)
Tower karst (fenglin) and cockpit karst (fengcong) are two globally important representative styles of tropical karst. Previously proposed sequential and parallel development models are preliminary, and geomorphological studies to date do not provide enough satisfactory evidence to delineate the spatial and temporal relation between the two landscapes. This unclear interpretation of tower-cockpit relationships not only obscures understanding of the process-form dynamics of these tropical karst landforms, but also confuses their definition. Moreover, previous technological limitations, as well as the fragmental nature of the karst landscapes, has limited incorporation of geologic and other data into broad geospatial frameworks based on geographic information science (GIS) and remote sensing (RS), with such data being spatially and temporally disparate. This study incorporates various data sources to address the fenglin-fengcong relationship, particularly the recently postulated "edge effect", which has not been examined in detail previously and which may hinge upon the interaction of multiple environmental variables, including geomorphology, vegetation and hydrology. To address these issues, this research combines geographic, geologic and hydrologic data, using GIS and RS technologies to test quantitatively the "edge effect" hypothesis. Specifically, there are four inter-related objectives of this study. The first is to develop a method to effectively differentiate fenglin and fengcong. The second is to extract optimally the vegetation information from satellite imagery, and investigate the correlation between tropical karst topography and its vegetation. The third is to combine the regional hydrologic data and solute transport models to estimate geochemicals control of fenglin and fengcong. The fourth one, perhaps the most important, is to test the "edge effect" hypothesis using the results from the other three objectives. There are several significant conclusions. First, DEM data are very useful for extracting profiles of complex surface landforms from satellite imagery. Second, the vegetation distribution varies between tower karst and cockpit karst and the differences correlate with topographic characteristics. The under-representation of vegetation on the south-southwest aspect of tower karst is remarkable, and its overall distribution is both less abundant and dispersed than in cockpit karst. Third, the "edge effect" exists in the Guilin area, with variable intensity and extension in different dimensions. In summary, the major contributions of the study include the following. First, the study has developed a method to classify fenglin-fengcong tropical karst effectively, even with the presence of shadows that would otherwise hinder traditional classification. Second, the study showed a variance of vegetation vitality within aspects of fenglin that might relate to its geomorphic difference from fengcong. Third, the study combined groundwater and solute transport models to estimate bicarbonate distributions, representing a novel systematic and quantitative approach to tropical karst studies.
Keywords: Cockpit Karst; Edge Effect; Guilin; Spatial Dimensions; Tower Karst